2020
DOI: 10.1080/22221751.2020.1778429
|View full text |Cite
|
Sign up to set email alerts
|

Roles of lncRNAs in influenza virus infection

Abstract: Recent studies have identified host long noncoding RNAs (lncRNAs) as key regulators of host-virus interactions during viral infection. The influenza A virus (IAV) remains a serious threat to public health and economic stability. It is well known that thousands of lncRNAs are differentially expressed upon IAV infection, some of which regulate IAV infection by modulating the host innate immune response, affecting cellular metabolism, or directly interacting with viral proteins. Some of these lncRNAs appear to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 76 publications
(94 reference statements)
0
21
0
Order By: Relevance
“…Although great progress has been made in the diagnosis and treatment for HCC, these achievements were far from improving the survival time and cure rate of HCC patients. More and more studies had shown that lncRNAs play an important role in various biological processes of human body (Wang et al 2020;Qu et al 2020;Lu et al 2020). In order to understand the development, diagnosis and treatment of the disease we need to explore the regulation mode of human gene deeply and immediately.…”
Section: Discussionmentioning
confidence: 99%
“…Although great progress has been made in the diagnosis and treatment for HCC, these achievements were far from improving the survival time and cure rate of HCC patients. More and more studies had shown that lncRNAs play an important role in various biological processes of human body (Wang et al 2020;Qu et al 2020;Lu et al 2020). In order to understand the development, diagnosis and treatment of the disease we need to explore the regulation mode of human gene deeply and immediately.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of lncRNA has been observed in many infectious diseases, especially in diseases caused by viral infection and reviewed [ 18 ]. Infections with influenza virus (IAV), HIV, herpes simplex virus (HSV), hepatitis C virus (HCV), hepatitis B virus (HBV), severe acute respiratory syndrome coronavirus (SARS-CoV) and others alter the expression of host lncRNA 19 , 20 . Expression of lncRNA EGOT, NEAT1, BISPR/LncBST2, LINC01191/VIN/lnc-ACTR3, ISR (IFN-stimulated lncRNA) 2 and ISR8, LOC100506319/LINC01988/LncRNA-PAAN, LOC102637961/lncRNA-ACOD1, MIR155HG, TSPOAP1-AS1, PSMB8-AS1, PSORS1C3, IVRPIE was increased and expression of NRAV/DYNLL1AS1 was decreased in IAV infected cells 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The known and the unknown lncRNA expression in EBOV, LPS and RESTV cells identi ed. Cellular lncRNAs which actively expressed during viral infections may help to promote the virus replications, suppress the antiviral immune response [34]. In total, 1581 known and 405 novel lncRNA identi ed.…”
Section: Discussionmentioning
confidence: 99%